Amos Tutuola’s Palm Wine Drinkard and the Challenges of Translating A Hybrid Literature - Ogbeide-Ihama, Mojisola A. (African Journal of Stability and Development (AJSD), 2018)
Literary translation is the art of recreating a literary text in another language while using the source text as a medium. Translation in contemporary times has gone beyond mere linguistic transfer: it is now a veritable means of cultural transfer. Language being the vehicle of culture, translation therefore consists in conveying in a target language concepts and symbolisms of culture through a system of representation. Every literary work being a cultural product, often resists translation. Thus, translating works from English speaking African literature proves to be a difficult task as it poses some peculiar challenges. The aim of this work is to examine the diverse challenges encountered in the process of translating the sense and the style of The Palm-Wine Drinkard, a novel written by Amos Tutuola and translated as L’ivrogne dans la brousse by Raymond Queneau. In order to facilitate our discussion, we will be doing a comparative analysis of the original version and its translated version. The study concludes that at the base of translation is culture and language and that no matter the challenges posed in the process of translation, one must endeavour to safeguard the linguistic and cultural specificity of the text as well as ensure that the source and the target texts communicate the same message.